MONITORING HEAVY METALS, MYCOTOXINS, COCCIDIOSTATS AND MICROBIAL CONTAMINATION IN ANIMAL FEED: A NORTH MACEDONIA STUDY (2018-2022) - Sandra Mojsova; Elizabeta Dimitrieska Stojkovikj; Biljana Stojanovska Dimzoska; Vangelica Enimiteva; Ljupco Angelovski; Zehra Hajrulai Musliu; Gordana Ilievska; Dushica Koceva; Aleksandra Angeleska (Macedonian Veterinary Review, 2025)
Feed contamination can occur at every stage of the feed chain, including manufacturing, storage, transport, and utilization. Ensuring feed safety is fundamental for livestock health, animal performance, and food safety throughout the feed-to-food chain. The study aimed to make qualitative and quantitative assessment of microbiological and chemical hazards in animal feed in North Macedonia from 2018 to 2022. A total of 1,629 feed samples were analysed for heavy metals, mycotoxins, and coccidiostats, whereas 598 samples were examined for microbial contamination. The results indicate a significant prevalence of heavy metals, with lead (Pb) detected in 100% of the samples, although mostly within regulatory limits. Mycotoxins, notably ochratoxin A (OTA) and aflatoxin B1 (AFB1), were also identified, with non-compliance in 10.88% of cattle feed for AFB 1. Coccidiostat residues exceeded the maximum levels in 4.6% of the samples. Microbiological analysis revealed that 1.34% of feed samples were contaminated with Salmonella spp., and 3.8% tested positive for sulphitereducing clostridia. The findings on both microbiological and chemical hazards indicate their potential to threaten the feed safety chain. Accordingly, this study emphasizes the need for continuous comprehensive feed safety monitoring and the enforcement of stringent safety regulations to safeguard animal and public health in North Macedonia.
Keywords: feed safety, contaminants, coccidiostats, microbiological hazards, North Macedonia